Introduction to Human Resource Management: A Guide to HR in Practice - Charles Leatherbarrow; Janet Fletcher (New York Kogan Page, 2019)
ntroduction to Human Resource Management is a comprehensive and accessible guide to the subject of HRM. Drawing on the authors' experiences in both the public and private sectors and underpinned by academic theory, this textbook follows the logical sequence of the employment cycle and shows how human resource management plays out in practice. It covers organizational culture, the role of the HR professional, HR planning, recruitment and selection, talent management, L&D, motivation and performance, health and safety, diversity and equality, employment law, change management and handling and managing information. With a range of pedagogical features, including contemporary case studies and review questions, Introduction to Human Resource Management maps to the CIPD Level 3 Foundation Certificate in HR Practice and is also ideal for foundation and undergraduate students encountering HRM for the first time. This fully updated 4th edition has been revised and expanded to include coverage of zero-hours contracts and the gig economy, social media and e-recruitment and the UK apprenticeship levy. Online supporting resources include an instructor's manual, lecture slides and students' resources including multiple choice questions, additional case studies and reflective questions for self-study.
Keywords: Personnel management; (ASB-2521) Leadership & HRM